1995
DOI: 10.1128/aem.61.1.44-47.1995
|View full text |Cite
|
Sign up to set email alerts
|

Marine Vibrio species produce the volatile organic compound acetone

Abstract: While screening aerobic, heterotrophic marine bacteria for production of volatile organic compounds, we found that a group of isolates produced substantial amounts of acetone. Acetone production was confirmed by gas chromatography, gas chromatography-mass spectrometry, and high-performance liquid chromatography. The major acetone producers were identified as nonclinical Vibrio species. Acetone production was maximal in the stationary phase of growth and was stimulated by addition of L-leucine but not the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Production can take place by photo‐degradation of dissolved organic matter [ Zhou and Mopper , 1997] and directly by phytoplankton and bacteria [ Nemecek‐Marshall et al , 1995]. Loss can take place by photo‐degradation or biotic consumption [ Mopper and Stahovec , 1986; Nemecek‐Marshall et al , 1995]. Two recent field campaigns support a biologically mediated acetone source in seawater.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production can take place by photo‐degradation of dissolved organic matter [ Zhou and Mopper , 1997] and directly by phytoplankton and bacteria [ Nemecek‐Marshall et al , 1995]. Loss can take place by photo‐degradation or biotic consumption [ Mopper and Stahovec , 1986; Nemecek‐Marshall et al , 1995]. Two recent field campaigns support a biologically mediated acetone source in seawater.…”
Section: Methodsmentioning
confidence: 99%
“…A major uncertainty in the budget of atmospheric acetone is the role of the ocean. Photochemical and biological processes in the ocean both produce and consume acetone [ Nemecek‐Marshall et al , 1995; Sinha et al , 2007; Zhou and Mopper , 1997]. Atmospheric acetone concentrations over the remote oceans are in the range of 200–500 pptv [ Singh et al , 2000], only a factor of 3–4 lower than over continental source regions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous budgets have ranged widely in the ocean's role, varying from a 21 Tg yr −1 source [ Jacob et al , 2002] to a 14 Tg yr −1 sink [ Singh et al , 2004]. Acetone can be produced in surface waters by the solar irradiation of dissolved organic matter [ Kieber et al , 1990; Zhou and Mopper , 1997] and by microbial metabolism [ Nemecek‐Marshall et al , 1995]. There have been limited observations of acetone in oceanic waters [ Zhou and Mopper , 1997; Williams et al , 2004] and the only direct flux measurements of acetone have been over land [ Shaw et al , 1998].…”
Section: Introductionmentioning
confidence: 99%
“…can cause poor growthhrvival performance of shrimp larvae in commercial hatcheries. It has been suggested that the mechanism influencing Q Copyright by the World Aquaculture Society 2005 larval mortality is related to the production of extracellular proteases and/or toxins from these bacterial strains (Long et al 1981;Nemeck-Marshal et al 1995).…”
Section: James N Sweeneymentioning
confidence: 99%